P. F. 1978 Helmer Fogedgaard / Zbigniew Dolatowski. - Dolatowski, Zbigniew (1927-2001) ([wydawca nieznany], 1978)
Wśród szuwarów, nad błękitną taflą wody pomarańczowa kula słońca, u dołu napis: P. F. 1978 Helmer Fogedgaard.